Regulation of protein metabolism by a physiological concentration of insulin in mouse soleus and extensor digitorum longus muscles. Effects of starvation and scald injury. - Frayn, K; Maycock, P (1979)
1. Although high concentrations of insulin affect both synthesis and degradation of skeletal-muscle protein, it is not known to what extent these effects occur with physiological concentrations. The effects of a physiological concentration of insulin (100 mu units/ml) on muscle protein synthesis, measured with [3H]tyrosine, and on muscle protein degradation, measured by tyrosine release in the presence of cycloheximide, were studied in mouse soleus and extensor digitorum longus muscles in vitro. 2. Insulin significantly stimualated protein synthesis in both muscles, but an inhibition of degradation was seen only in the extensor digitorum longus. 3. Starvation for 24 h decreased the rate of protein synthesis and increased the rate of breakdown in the extensor digitorum longus. Sensitivity to insulin-stimulation of proteins synthesis in the soleus was increased by starvation. 4. ;a 20%-surface-area full-skin-thickness dorsal scald injury produced a fall in total protein content in soleus and extensor digitorum muscles, maximal on the third day after injury. Soleus muscles 2 days after injury showed an impairment of protein synthesis; degradation was unaffected and neither synthesis nor degradation in vitro was significantly affected in the extensor digitorum longus. 5. The advantages and limitations of studies of protein metabolism in vitro are discussed.